Kontribusi Program Tahfidzul Qur’an Jurusan Agama Dalam Mengembangkan Manajemen Pendidikan Berbasis Pesantren MA Al-Amiriyyah Blokagung Tegalsari Banyuwangi - M. Khozin Kharis (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
The purpose of this study are: (1) To determine the application of the Qur'an Tahfidzul program; (2) To determine the contribution of the program Tahfidzul Quran religion majors in developing schools based education management. This research uses qualitative research data triangulation analysis techniques. For information, researchers use interviewing techniques, observation, and documentation. The results showed that: (1) the efforts made Madrasah Aliyah al-Amiriyyah in developing pesantren based education management is through religion in the department tahfid program, beginning with the steps in the implementation of the program Tahfidzul Koran, followed by application of the method; (2) Contributions Program Tahfidzul Qur'an Religious Programs In Developing Pesantren-Based Education Management are: a) Character education, Maintaining the traditional character, Maintaining cultural, religious education Implement. b) The concept of schools based education: Improving the quality of morality, civilization Build quality in accordance with the values of Islam in the future, Sustaining development and guidance on all aspects of the student's personal terms of intellectual, psychological, social, and spiritual